2013
DOI: 10.1155/2013/694368
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Release in Pristine and Drained Peat Profiles in Response to Water Table Fluctuations: A Mesocosm Experiment

Abstract: In the northern hemisphere, variability in hydrological conditions was suggested to increase as a consequence of climate warming, which may result in longer droughts than the area has experienced before. Due to their predominately anoxic conditions, peatlands are expected to respond to changes in hydrological conditions, such as successive drying and rewetting periods. As peatlands are rich in organic matter, any major changes in water table may influence the decomposition of it. The hydrological conditions ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…The further reduction of soil moisture possibly limited nitrogen mineralization, resulting in much lower NMR afterward this period. Similar to what other studies found (Dominik and Jörg, 2007;Frank et al, 2014;Laine et al, 2013), ammonium was the dominant inorganic nitrogen and gradually accumulated in peat during drought (Figs. 1c,d).…”
Section: Discussionsupporting
confidence: 91%
“…The further reduction of soil moisture possibly limited nitrogen mineralization, resulting in much lower NMR afterward this period. Similar to what other studies found (Dominik and Jörg, 2007;Frank et al, 2014;Laine et al, 2013), ammonium was the dominant inorganic nitrogen and gradually accumulated in peat during drought (Figs. 1c,d).…”
Section: Discussionsupporting
confidence: 91%
“…In Löytynoja, nutrient and carbon concentrations changed along the hydrological pathway from upstream to downstream due to the land-use of the sampling points (Table 1). Dissolved organic carbon as well as ammonium increased from the forest-dominated S1 to the S3 and S4, where peatland contributed more to the water quality, agreeing with the previous findings on the higher proportion of peatland in the catchment increasing DOC concentrations (Huotari et al 2013;Laine et al 2014), and on high ammonium loading coming from drained peatlands (Laine et al 2013;Arvola et al 2015). Nitrite + nitrate, phosphate, TN and TP peaked at agriculture-dominated S2, as observed previously in Löytynoja and in other agriculture-affected streams (Hakala et al 2002;Inwood et al 2005).…”
Section: Environmental Variables and Denitrification Ratessupporting
confidence: 91%
“…Before rewetting there was no NH 4 -N in the peat, only NO 3 -N. Four years of rewetting raised NH 4 -N concentrations above 100 mg kg -1 dw, while NO 3 -N decreased to levels below 1 mg kg -1 dw probably dependent on anoxic conditions. NO 3 -N production stops at rewetting and instead the peat organic matter starts to release ammonium (Laine et al 2013). Pool of NO 3 would partly be denitrified and also taken up by plants increasing in coverage after 5-10 years.…”
Section: Effects On the Peat Chemistrymentioning
confidence: 99%